Practical high-performance lead-free piezoelectrics: structural flexibility beyond utilizing multiphase coexistence. Issue 2 (5th November 2019) - Liu, Qing; Zhang, Yichi; Gao, Jing; Zhou, Zhen; Yang, Dong; Lee, Kai-Yang; Studer, Andrew; Hinterstein, Manuel; Wang, Ke; Zhang, Xiaowen; Li, Longtu; Li, Jing-Feng
Abstract: Due to growing concern for the environment and human health, searching for high-performance lead-free piezoceramics has been a hot topic of scientific and industrial research. Despite the significant progress achieved toward enhancing piezoelectricity, further efforts should be devoted to the synergistic improvement of piezoelectricity and its thermal stability. This study provides new insight into these topics. A new KNN-based lead-free ceramic material is presented, which features a large piezoelectric coefficient ( d 33 ) exceeding 500 pC/N and a high Curie temperature ( T c ) of ∼200°C. The superior piezoelectric response strongly relies on the increased composition-induced structural flexibility due to lattice softening and decreased unit cell distortion. In contrast to piezoelectricity anomalies induced via polymorphic transition, this piezoelectricity enhancement is effective within a broad temperature range rather than a specific small range. In particular, a hierarchical domain architecture composed of nano-sized domains along the submicron domains was detected in this material system, which further contributes to the high piezoelectricity.